Determination of the profile of DO and its mass transferring coefficient in a biofilm reactor packed with semi-suspended bio-carriers. (October 2017) - Tang, Bing; Song, Haoliang; Bin, Liying; Huang, Shaosong; Zhang, Wenxiang; Fu, Fenglian; Zhao, Yiliang; Chen, Qianyu
Graphical abstract: Highlights: A novel semi-suspended bio-carrier was designed and used in a biofilm reactor. Profile of DO and its mass transfer coefficient in the reactor were determined. Biofilm is easier to attach and grow on the semi-suspended bio-carrier. The contents of EPS in the biofilm have a close relationship with the Db of DO. Abstract: The work aims at illustrating the profile of DO and its mass transferring process in a biofilm reactor packed with a novel semi-suspended bio-carrier, and further revealing the main factors that influence the mass transferring coefficient of DO within the biofilm. Results showed that the biofilm was very easy to attach and grow on the semi-suspended bio-carrier, which obviously changed the DO profile inside and outside the biofilm. The semi-suspended bio-carrier caused three different mass transfer zones occurring in the bioreactor, including the zones of bulk solution, boundary layer and biofilm, in which, the boundary layer zone had an obvious higher mass transfer resistance. Increasing the aeration rate might improve the hydrodynamic conditions in the bioreactor and accelerate the mass transfer of DO, but it also detached the biofilm from the surface of bio-carrier, which reduced the consumption of DO, and accordingly, decreased the DO gradient in the bioreactor.